Angkut.in : The Future of Trucking by Digital Product Design Journey: english - Suryawijaya, Tito; Safitri, Maria (Asian Journal of Innovation and Entrepreneurship, 2024)
Jepara Regency in Central Java, Indonesia, is renowned as the "World Carving Center" due to its flourishing furniture carving industry. Despite successfully exporting carvings globally, the distribution process encounters challenges with conventional methods, primarily due to a limited truck fleet exacerbated by the post-pandemic situation. This study aims to scrutinize the effectiveness of "Angkut.in" as an innovative solution for overcoming hurdles in heavy goods distribution, particularly furniture. Utilizing Design Thinking, the research incorporates an analysis of the application of the Technology Acceptance Model (TAM) and digital marketing strategies within the "Angkut.in" application design. Employing a Supply Chain Management (SCM) approach, the research assesses the application's impact on local innovation growth, operational efficiency, and the competitiveness of the furniture industry. Market analysis indicates a focus on the online furniture entrepreneur segment. The marketing strategy involves real-time tracking services, live price checking, and user-friendly application interfaces. The business model adopts a Business-to-Business (B2B) approach, emphasizing transportation services for large goods businesses. The business identity design encompasses color selection, typography, and graphic elements that mirror the innovative and reliable nature of goods delivery services. Risk analysis covers technological factors, market competition, loss of goods, data security, capital limitations, regulatory changes, market acceptance, and force majeure. Angkut.In is categorized as a low-risk business according to the risk analysis matrix. The prototype validation by UKM Partners yielded a score of 8.5 out of 10, indicating maturity and compliance with most evaluation criteria. The provided fix notes will guide further development steps before the official launch.